2017
DOI: 10.1016/j.cmet.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Glycogenin Causes Glycogen Accumulation and Muscle Function Impairment

Abstract: Glycogenin is considered essential for glycogen synthesis, as it acts as a primer for the initiation of the polysaccharide chain. Against expectations, glycogenin-deficient mice (Gyg KO) accumulate high amounts of glycogen in striated muscle. Furthermore, this glycogen contains no covalently bound protein, thereby demonstrating that a protein primer is not strictly necessary for the synthesis of the polysaccharide in vivo. Strikingly, in spite of the higher glycogen content, Gyg KO mice showed lower resting en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 39 publications
4
59
1
Order By: Relevance
“…In addition, the protein acquired a C-terminal glycogen synthase binding domain of unknown function (Fig. 3A; Zequiraj et al, 2014) Past and recent studies indicate that, despite the compelling in vitro data, glycogenin is not required for glycogen synthesis in yeast and mice (Torija et al, 2005;Testoni et al, 2017). Nevertheless, glycogen levels are affected in a manner that is currently unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the protein acquired a C-terminal glycogen synthase binding domain of unknown function (Fig. 3A; Zequiraj et al, 2014) Past and recent studies indicate that, despite the compelling in vitro data, glycogenin is not required for glycogen synthesis in yeast and mice (Torija et al, 2005;Testoni et al, 2017). Nevertheless, glycogen levels are affected in a manner that is currently unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen synthesis is initiated by GN ( Figure 3), which catalyzes the transfer of glucose residues from UDP-glucose to Tyr-194 of a separate GN molecule, thereby forming α-1, 4-glycosidic linkages to create a linear glucose polymer of approximately 10-20 glucose residues. 49 In humans, there are two GN isoforms. GN1 (encoded by the GYG1 gene) is widely expressed, whereas GN2 (encoded by the GYG2 gene) is primarily located in human liver.…”
Section: Initiation Of Glycogen Synthesismentioning
confidence: 99%
“…14 Liver glycogen is involved in maintaining blood glucose homeostasis. 20,21 Therefore, in the current review, we will not focus on SM glycogen. In diabetic mouse liver, it has been shown that the α particles of glycogen are molecularly fragile over the feeding and fasting cycle: they easily degrade into small β particles in the presence of dimethyl sulfoxide (DMSO), which is an H-bond disruptor.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of a de novo glycogen granule is thought to be initiated by glycogenin. Glycogenin glycosylates itself at a tyrosine residue and catalyzes the extension of glycan chains (Cao, Mahrenholz, DePaoli‐Roach, & Roach, ; Smythe & Cohen, ), although recent studies with glycogenin‐deficient mice indicate other mechanisms are likely possible (Testoni et al, ). The glycan chains then serve as a primer for glycogen synthetase, which catalyzes the formation of α‐1, 4‐glycosidic linkages of glycogen.…”
Section: Glycogen Metabolismmentioning
confidence: 99%